The Effects of a CRA-I Intervention on Students’ Number Sense and Understanding of Addition - Flores, Margaret M.; Hinton, Vanessa M. (Remedial and special education, 2022)
As students develop understanding and fluency in single-digit operations such as addition, they develop sophisticated strategies and number sense (magnitude, number order, and composition). Deficits in number sense and reliance on inefficient approaches can lead to struggle in mathematics. Intervention research in this area reported effects on students’ automaticity. Research reported observational data regarding strategy-use, but not growth in number sense and understanding of operations. This study investigated the effects of an intervention using the concrete-representational-abstract-integrated (CRA-I) sequence. The purpose of this study was to assess the effects of CRA-I on students’ number knowledge (magnitude, place value, and flexibility in strategy-use) and understanding of addition (commutative property and relation to subtraction). The researchers used a multiple probe across participants design. In addition, the researchers collected descriptive data on students’ automaticity. There was a functional relation between CRA-I and students’ number sense and understanding of addition, and students’ automaticity increased.